Rancang Bangun dan Implementasi Aplikasi Śiva Purāṇa di IAHN Tampung Penyang Palangka Raya - Muliana, I Ketut Agus (LPPM POLITEKNIK LP3I BANDUNG, 2023)
Applications of digital Hindu scriptures are still limited. At on the other hand, the Vedic scriptures are not a single book that consists of various books with a very large number of slokas (verses) that make it not possible to be studied manually. Selection of the book of Śiva Purāṇa to be developed into a digital application has four reasons namely: Hinduism in Indonesia Saiva Siddhanta, one of whose guidelines is the book of Śiva Purāṇa. Purāṇa is a means of transmission before studying the other Vedic scriptures, the vastness of the teachings in the Śiva Purāṇa other Vedic scriptures, the vastness of the teachings in Śiva Purāṇa which consists of 100,000 slokas, and the the limited physical book of Śiva Purāṇa. This research seeks to develop a application of digital Hindu scriptures, especially the book of Śiva Purāṇa. This research uses a Research and Development approach with Software Development Life Circle software development method and Waterfall development model. Data collection techniques in this study used literature studies, observation and interviews. This research successfully produced the Śiva Purāṇa application for android platform